The Human Bioenergy Field Detected by a Torsion Pendulum? The Effect of Shielding and a Possible Conventional Explanation - van den Berg, Willem (Journal of Scientific Exploration, 2015)
J. N. Hansen and J. A. Lieberman (2009, 2013) at the University of Maryland have published accounts of their use of a simple and inexpensive torsion pendulum to detect and measure a time-varying force exerted by the human head. In view of control experiments intended to rule out conventional explanations in the form of electrostatic or convective forces, they suggest that this force may be due to a "field of bio-energy...[that] is the basis of many forms of traditional medicine that have been practiced for thousands of years" but which has heretofore been undetectable by science (Hansen and Lieberman 2013). We have replicated their basic results using similar equipment (Hansen 2013a), furthermore ruling out magnetic forces and using a different means of ruling out electrostatics. However, we found that the use of a specially constructed plastic shield to more rigorously rule out convection from the warm human head entirely eliminates the external torque on the pendulum. It therefore appears that either the origin of the force is convective, or else the material of which the shield is made blocks the human bioenergy field.